2000
DOI: 10.4319/lo.2000.45.2.0436
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial production and growth efficiencies: Direct measurements on riverine aggregates

Abstract: Heterotrophic bacteria transform organic matter by respiration and production of new biomass. Because there are only a limited number of studies on the respiration of bacteria attached to particulate organic matter, their role in the carbon cycle of aquatic systems is not well known. In this study, we combine radiotracer with microsensor techniques to measure bacterial production and respiration rates on the same aggregate and to directly determine the growth efficiency of the microbial community attached to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…The integrated PAB productivity was up to 1.8 times higher than that of PP. These values were higher than values reported for the temperate region (Williams 1981, Cole et al 1988), but were closer to that reported for the Indus River delta (Bano et al 1997).Particles are known to be preferential sites for bacterial colonization (Grossart & Ploug 2000). The cumulative carbon flux into bacteria, or bacterial carbon demand (BCD) is the ratio of BP to the bacterial growth efficiency (BGE).…”
supporting
confidence: 53%
See 4 more Smart Citations
“…The integrated PAB productivity was up to 1.8 times higher than that of PP. These values were higher than values reported for the temperate region (Williams 1981, Cole et al 1988), but were closer to that reported for the Indus River delta (Bano et al 1997).Particles are known to be preferential sites for bacterial colonization (Grossart & Ploug 2000). The cumulative carbon flux into bacteria, or bacterial carbon demand (BCD) is the ratio of BP to the bacterial growth efficiency (BGE).…”
supporting
confidence: 53%
“…Particles are known to be preferential sites for bacterial colonization (Grossart & Ploug 2000). The cumulative carbon flux into bacteria, or bacterial carbon demand (BCD) is the ratio of BP to the bacterial growth efficiency (BGE).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations